Simulacra and the Aesthetics of Fashion Marketing on In-stagram: A Case Study of Indonesian Local Brands - Rinaldi Bursan (International Forum of Researchers and Lecturers, 2026)
By examining how visual aesthetics play a crucial role in creating a hyperreal symbolic reality, this study critically investigates the creation and consumption of simulacra in the Instagram marketing of regional Indonesian fashion firms. This study shows that local brands actively create representational worlds that negotiate identity between claims of locality and global aesthetic standards, in addition to selling products, using an interpretative qualitative approach that combines netnography, visual semiotic analysis, and in-depth interviews with brand managers and consumers. According to the research, rigorous visual curation techniques result in what are known as ethical simulacra, in which ideals like sustainability and community support are reduced to beautiful pictures divorced from tangible behaviors. In addition to examining ethical conundrums in netnographic research within ambivalent digital settings, this analysis emphasizes the critical role that Instagram's algorithms play as non-human actors that influence aesthetic canons. By highlighting distinctive dynamics including self-exoticization tactics and modernity paradoxes that influence symbolic consumption patterns, this study theoretically advances Consumer Culture Theory and critical marketing by concentrating on the Indonesian setting. The study's findings suggest a more ethical and thoughtful approach to marketing when confronting the logic of digital hyperreality.